Changing Constellations of Southeast Asia : From Northeast Asia to China - Pieterse, Jan Nederveen; Embong, Abdul Rahman; Tham, Siew Yean. (London : Taylor and Francis, 2017)
"Southeast Asia is among emerging economies that have become important drivers of the world economy. ASEAN has furthered the region's economic integration. Yet, growth remains dependent on foreign investment. Inequality has grown or remained high. Democracy, instead of consolidating, has stalled or regressed. Changing Constellations of Southeast Asia seeks to:Shed light on the gap between Northeast Asia and Southeast Asia from a variety of viewpoints, across trade and industry, services and education and language policies;Examine institutions and elite capture to understand why middle-tier Southeast Asian countries have failed in following the 'East Asian miracle';Examine China's growing influence and how this growing role affects Southeast Asia as a constellation. Contributing to critical political economy and comparative development studies in East Asia, this timely volume will appeal to undergraduate and postgraduate students interested in Southeast Asia studies, International Political Economy, Development sociology and economics, Social Policy and Asian Politics."--Provided by publisher.
Chapter Introduction / JAN NEdiferVEEN PIETERSE , ABDUL RAHMAN -- part PART I Southeast and Northeast Asia -- chapter 1 What happened to the Miracle Eight? Looking East in the twenty- first century / JAN NEdiferVEEN PIETERSE -- chapter 2 Dynamics of trade in Factory Asia: Value added / ANDREW JIA Y I KAM -- chapter 3 Higher education in Southeast Asia / FAZAL RIZVI -- chapter 4 The rise of Global English and language policies of China, Japan, Thailand and Malaysia / China, Japan, Thailand and Malaysia ZAWIAH YAHYA -- part PART II Institutions -- chapter 5 Diversity of Southeast Asian capitalisms: evolving state- business relations in Malaysia / EDMUND TERENCE GOMEZ AND ELSA LAFAYE D E -- chapter 6 How to escape the transformation trap: building social consensus for sustainable development MARC S AX ER -- chapter 7 Thailand: Exception to the rule or rule by exception? / TIM RACKETT -- part PART III Southeast Asia and China -- chapter 8 Changing constellations of Southeast Asia / JAN NEdiferVEEN PIETERSE -- chapter 9 The charms of China{u2019}s New Silk Road: Connecting the dots in Southeast Asia / ABDUL RAHMAN EMBONG -- chapter 10 Examining the shift to services: Malaysia and China compared / SIEW YEAN THAM -- chapter 11 Economic diplomacy in ASEAN: The case of Myanmar and China investment relations / SUFIAN JUSOH -- chapter 12 Southeast Asia and China relations: desecuritizing the RASHILA RAMLI / South China Sea.
OCLC-licensed vendor bibliographic record.
Keywords: SOCIAL SCIENCE -- Sociology -- General; Southeast Asia -- Politics and government -- 1945-